Pengaruh knowledge sharing dan self-efficacy terhadap employee performance melalui job satisfaction pada karyawan - Hafizh Nasrulloh; Muhammad Husain (Jurnal Ilmu Manajemen, 2025)
PT X is one of the operational regions that plays a vital role in supporting transportation services in Indonesia. Employee performance is a crucial factor in ensuring optimal service delivery. This study aims to examine and explain the influence of knowledge sharing and self-efficacy on employee performance through job satisfaction at PT X. The research employs a quantitative approach with non-probability purposive sampling, involving 40 employees as respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.2.9. The results indicate that both knowledge sharing and self-efficacy have a positive and significant influence on job satisfaction. Additionally, self-efficacy directly influences employee performance. However, knowledge sharing does not directly affect employee performance. Furthermore, job satisfaction significantly affects employee performance and mediates the relationship between knowledge sharing and performance. Conversely, job satisfaction does not mediate the influence of self-efficacy on performance. These findings suggest that enhancing job satisfaction can strengthen the positive impact of knowledge sharing on employee performance, while self-efficacy independently contributes to performance outcomes. The study highlights the importance of fostering a collaborative knowledge culture and building employee confidence to improve organizational effectiveness.